KOMPARASI STRUCTURE EXERCISE METHOD DAN DRILL TERHADAP PEMAHAMAN KONSEP PADA MATERI STOIKIOMETRI - Ulvi Nikmawati M; Fitri - Refelita; Arif - Yasthophi (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
This research aimed at knowing whether there was or not a difference on student concept comprehension taught by using Guided Discovery Learning model with Structure Exercise method that was compared with taught by using Guided Discovery Learning model with Drill method on Stoichiometry.  This study was conducted in SMA Negeri 1 Tambang in academic 2018/2019. This research was a Quasi-experiment with pretest and posttest design. Purposive sampling technique was used, and it was obtained two sample classes—the tenth-grade students of class MIA 2 (experimental class one) and MIA 3 (exsperimental class two). The data of observation results and student concept comprehension were tested by using independent sample t-test.  Based on the data analysis, it was obtained -ttable ≤ tobserved ≤ +ttable (-1.68<2.24>1.68). Thus, there was a significant difference on student concept comprehension between Guided Discovery Learning model with Structure Exercise and Guided Discovery Learning model with Drill method variables on Stoichiometry material at the tenth grade of State Senior High School 1 Tambang, mean score of student concept comprehension at the tenth grade of MIA 2 was 0.74 and the score of MIA 3 was 0.66.